Titanium-molybdenum-based antifriction wear-resistant coating and preparation method thereof

By laying a titanium-molybdenum-based friction-reducing and wear-resistant coating on the surface of the metal material, using wear-resistant sub-layers of titanium-molybdenum copper nitrogen and titanium-molybdenum nitrogen and lubricating layers of materials such as graphite, the problems of high friction coefficient, low hardness and poor wear resistance of existing metal materials are solved, and the coating effect of high hardness, low friction and low wear rate is achieved.

CN119615059APending Publication Date: 2025-03-14XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411806251.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the industrial fields of aerospace, new energy vehicles, wind power, existing metal materials have high friction coefficient, low hardness and poor wear resistance, which cannot meet the needs of high performance and high reliability.

Method used

A titanium-molybdenum-based friction-reducing and wear-resistant coating is adopted. By stacking transition layers, connection layers, multi-layer main wear-resistant layers and lubricating layers, a wear-resistant sub-layer of different materials such as titanium-molybdenum copper nitrogen and titanium-molybdenum nitrogen is formed, and a lubricating layer of materials such as graphite is combined to improve the hardness and wear resistance of the coating.

Benefits of technology

The coating has high hardness (1600 Vickers hardness or above), low friction coefficient (below 0.15) and low wear rate (below 2.5×10-6mm3/Nm), and has good friction reduction, wear resistance and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615059A_ABST
    Figure CN119615059A_ABST
Patent Text Reader

Abstract

The invention provides a titanium-molybdenum-based antifriction wear-resistant coating and a preparation method, and belongs to the technical field of alloy material surface treatment. The titanium-molybdenum-based antifriction wear-resistant coating comprises a transition layer, a connecting layer, a plurality of main wear-resistant layers and a lubricating layer which are sequentially arranged on one side of the substrate in a stacked mode. The main wear-resistant layer comprises a first wear-resistant sub-layer and a second wear-resistant sub-layer which are stacked; wherein the first wear-resistant sub-layer and the second wear-resistant sub-layer are made of different materials. The titanium-molybdenum-based antifriction wear-resistant coating has good lubricating, wear-resistant and corrosion-resistant effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of surface treatment of alloy materials, and in particular to a titanium-molybdenum-based anti-friction and wear-resistant coating and a preparation method thereof. Background Art

[0002] With the development of aerospace, new energy vehicles, wind power and other industrial fields, my country's demand for high-performance, high-reliability wear-resistant metals is becoming increasingly strong. The key components of motors, transmissions, transmission parts, drives and other devices must have excellent friction reduction and wear resistance to ensure long-term and stable operation of the equipment. However, most metal materials, such as titanium alloys, stainless steel, bearing steel, cast iron, and cemented carbide, not only have too high a friction coefficient, but also have low hardness and poor wear resistance, and can no longer meet the increasingly demanding design and use requirements. It can be seen that friction reduction and anti-wear work are of great significance to the high-quality development of my country's industry.

[0003] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a titanium-molybdenum-based anti-friction and wear-resistant coating and a preparation method thereof, so that the titanium-molybdenum-based anti-friction and wear-resistant coating has good lubrication, wear resistance and corrosion resistance.

[0005] According to a first aspect of the present disclosure, there is provided a titanium-molybdenum-based anti-friction and wear-resistant coating, comprising a transition layer, a connecting layer, a multi-layer main wear-resistant layer and a lubricating layer stacked in sequence on one side of a substrate;

[0006] The main wear-resistant layer includes a first wear-resistant sub-layer and a second wear-resistant sub-layer stacked on the connecting layer; wherein the first wear-resistant sub-layer and the second wear-resistant sub-layer are made of different materials.

[0007] According to one embodiment of the present disclosure, the first wear-resistant sub-layer is a titanium, molybdenum, copper and nitrogen layer; and the second wear-resistant sub-layer is a titanium, molybdenum and nitrogen layer.

[0008] According to an embodiment of the present disclosure, in the same main wear-resistant layer, the thickness of the first wear-resistant sub-layer is between 100 and 400 nanometers, and the thickness of the second wear-resistant sub-layer is between 100 and 300 nanometers.

[0009] According to one embodiment of the present disclosure, the thickness of the main wear-resistant layer is between 200 and 600 nanometers; and the thickness ratio of the second wear-resistant sub-layer to the first wear-resistant sub-layer is between 0.5 and 3.

[0010] According to one embodiment of the present disclosure, the number of the main wear-resistant layers is between 8 and 15.

[0011] According to one embodiment of the present disclosure, the thickness of the transition layer is between 100 and 320 nanometers; the thickness of the connecting layer is between 100 and 800 nanometers; and the thickness of the lubricating layer is between 1.6 and 3.9 micrometers.

[0012] According to one embodiment of the present disclosure, the material of the substrate is at least one of titanium alloy, stainless steel, bearing steel, cast iron or cemented carbide.

[0013] According to one embodiment of the present disclosure, the total thickness of the titanium-molybdenum-based anti-friction and wear-resistant coating is between 4.4 and 9.1 microns.

[0014] According to one embodiment of the present disclosure, the hardness of the titanium-molybdenum-based anti-friction and wear-resistant coating is above 1600 Vickers hardness, the friction coefficient of the titanium-molybdenum-based anti-friction and wear-resistant coating is below 0.15, and the wear rate of the titanium-molybdenum-based anti-friction and wear-resistant coating is below 2.5×10 -6 mm 3 / Nm or less.

[0015] According to another aspect of the present disclosure, a method for preparing a titanium-molybdenum-based anti-friction and wear-resistant coating is provided, comprising:

[0016] providing a substrate;

[0017] In a vacuum chamber, preparing a transition layer on the substrate;

[0018] Wherein, the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon gas channel, and a nitrogen gas channel;

[0019] Prepare a connection layer on a side of the transition layer away from the substrate;

[0020] At least one main wear-resistant layer is prepared on a side of the connecting layer away from the transition layer; wherein any one of the main wear-resistant layers comprises a first wear-resistant sub-layer and a second wear-resistant sub-layer which are stacked;

[0021] A lubricating layer is prepared on a side of the main wear-resistant layer away from the connecting layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0023] Figure 1 Schematic diagram of the film layer structure of the coating in the embodiment of the present disclosure.

[0024] Figure 2 This is a schematic diagram of a method for preparing a coating in an embodiment of the present disclosure.

[0025] Figure 3 The wear scar morphology of the coating surface in the embodiment of the present disclosure.

[0026] Figure 4 This is a schematic diagram of the wear scar morphology on the coating surface in Comparative Example 1.

[0027] Explanation of the accompanying drawings: 1. substrate; 2. transition layer; 3. connection layer; 4. main wear-resistant layer; 41. first wear-resistant sub-layer; 42. second wear-resistant sub-layer; 5. lubricating layer. DETAILED DESCRIPTION

[0028] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.

[0029] Although relative terms such as "upper" and "lower" are used in this specification to describe the relative relationship of one component of the illustration to another component, these terms are used in this specification only for convenience, such as according to the orientation of the examples described in the drawings. It is understood that if the device of the illustration is turned upside down, the component described as "upper" will become the component "lower". When a structure is "on" other structures, it may mean that the structure is formed integrally on the other structure, or that the structure is "directly" disposed on the other structure, or that the structure is "indirectly" disposed on the other structure through another structure.

[0030] In the related art, the following processes are often used to prepare friction-reducing and wear-resistant coatings: First, the traditional coating process, for example, electroplating hard chrome or nickel, carburizing, nitriding, etc. on the surface of the workpiece. The friction-reducing and wear-resistant layer prepared by this process is relatively low in hardness, generally lower than 1000HV (Vickers hardness), and the wear-resistant efficiency is limited, and the lubrication and friction-reducing effect cannot be produced. Second, the coating process such as spraying and laser cladding is used. This process has a greater impact on the size of the workpiece, requires subsequent processing, affects the processing efficiency of the workpiece, and the processed coating has a higher porosity. At the same time, the thermal impact of the preparation process is greater, and the risk of cracking of the coating is higher. Third, the use of polymer coating layers such as polyimide and polyethylene. Although this process can obtain better lubrication and friction-reducing effects, it has poor durability and there is a problem of insufficient bonding performance between the coating and the substrate (workpiece). Fourth, self-lubricating metal sleeves such as copper and silver are assembled on the surface of the workpiece to reduce the friction coefficient. This process increases the design and manufacturing process of the workpiece, and in the long-term use process, copper and silver are prone to deformation, adhesion and jamming, which will cause equipment failure and a lower service life.

[0031] Based on this, the embodiment of the present disclosure provides a titanium-molybdenum-based anti-friction and wear-resistant coating. Figure 1 The titanium-molybdenum-based anti-friction and wear-resistant coating includes a transition layer 2, a connecting layer 3, a multi-layer main wear-resistant layer 4 and a lubricating layer 5 stacked in sequence on one side of a substrate 1; the main wear-resistant layer 4 includes a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 stacked in layers; wherein the first wear-resistant sub-layer 41 and the second wear-resistant sub-layer 42 are made of different materials.

[0032] It should be noted that in the embodiment of the present disclosure, the titanium-molybdenum-based friction-reducing and wear-resistant coating includes a transition layer 2, a connecting layer 3, a first wear-resistant sub-layer 41, a second wear-resistant sub-layer 42, a first wear-resistant sub-layer 41, a second wear-resistant sub-layer 42... a first wear-resistant sub-layer 41, a second wear-resistant sub-layer 42 and a lubricating layer 5 which are sequentially stacked on one side of a substrate 1.

[0033] As an example, the titanium-molybdenum-based anti-friction and wear-resistant coating is composed of a transition layer 2, a connecting layer 3, a multi-layer main wear-resistant layer 4 and a lubricating layer 5 which are sequentially stacked on one side of a substrate 1.

[0034] In the embodiment of the present disclosure, the main wear-resistant layer 4 includes a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42, and the first wear-resistant sub-layer 41 and the second wear-resistant sub-layer 42 are made of different materials, and a lubricating layer 5 is provided on the main wear-resistant layer 4. Such a configuration enables the first wear-resistant sub-layer 41 and the second wear-resistant sub-layer 42 to interact with each other, which helps to obtain a coating with high hardness and high wear resistance; at the same time, a lubricating layer 5 is provided on the main wear-resistant layer 4, which can isolate the wear part from direct contact with the main wear-resistant layer 4 on the one hand; on the other hand, the lubricating layer 5 can protect the main wear-resistant layer 4 by using its own characteristics, so as to reduce the risk of premature damage to the main wear-resistant layer 4 and increase the service life of the coating.

[0035] In one embodiment of the present disclosure, the first wear-resistant sub-layer 41 is a titanium, molybdenum, copper, and nitrogen layer. For example, the first wear-resistant sub-layer 41 can be formed by depositing titanium, molybdenum, and copper in an atmosphere containing nitrogen.

[0036] In one embodiment of the present disclosure, the second wear-resistant sub-layer 42 is a titanium-molybdenum-nitrogen layer. For example, the second wear-resistant sub-layer 42 can be formed by depositing titanium-molybdenum in an atmosphere containing nitrogen.

[0037] In one example, the first wear-resistant sub-layer 41 is a titanium, molybdenum, copper and nitrogen layer; and the second wear-resistant sub-layer 42 is a titanium, molybdenum and nitrogen layer.

[0038] In one embodiment of the present disclosure, in the same main wear-resistant layer 4, the thickness of the first wear-resistant sublayer 41 is between 100 and 400 nanometers. For example, the thickness of the first wear-resistant sublayer 41 is 100 nanometers, 150 nanometers, 200 nanometers, 250 nanometers, 300 nanometers or 400 nanometers. It should be noted that in other embodiments of the present disclosure, the thickness of the first wear-resistant sublayer 41 is not limited thereto.

[0039] In one embodiment of the present disclosure, in the same main wear-resistant layer 4, the thickness of the second wear-resistant sublayer 42 is between 100 and 300 nanometers. For example, the thickness of the second wear-resistant sublayer 42 is 100 nanometers, 150 nanometers, 200 nanometers, 250 nanometers or 300 nanometers. It should be noted that in other embodiments of the present disclosure, the thickness of the second wear-resistant sublayer 42 is not limited thereto.

[0040] As an example, in the same main wear-resistant layer 4 , the thickness of the second wear-resistant sub-layer 42 is between 100 and 300 nanometers, and the thickness of the first wear-resistant sub-layer 41 is between 100 and 400 nanometers.

[0041] In one embodiment of the present disclosure, the thickness of the main wear-resistant layer 4 is between 200 and 600 nanometers. For example, the thickness of the main wear-resistant layer 4 is 200 nanometers, 300 nanometers, 400 nanometers, 500 nanometers or 600 nanometers. In other embodiments of the present disclosure, the thickness of the main wear-resistant layer 4 is not limited thereto.

[0042] In one embodiment of the present disclosure, the thickness ratio of the second wear resistant sublayer 42 to the first wear resistant sublayer 41 is between 0.5 and 3. For example, the thickness ratio of the second wear resistant sublayer 42 to the first wear resistant sublayer 41 is 0.5, 1.0, 1.5, 2.0, 2.5 or 3. In other embodiments of the present disclosure, the thickness ratio of the second wear resistant sublayer 42 to the first wear resistant sublayer 41 is not limited thereto.

[0043] As an example, the thickness of the main wear-resistant layer 4 is between 200 and 600 nanometers; the thickness ratio of the second wear-resistant sub-layer 42 to the first wear-resistant sub-layer 41 is between 0.5 and 3. By reasonably setting the thickness between the first wear-resistant sub-layer 41 and the second wear-resistant sub-layer 42, a balance can be achieved between the thickness of the coating and the thickness of the main wear-resistant layer 4, thereby improving the processing efficiency while making the coating have higher hardness and wear resistance.

[0044] In one embodiment of the present disclosure, the number of the main wear-resistant layers 4 is between 8 and 15. For example, the number of the main wear-resistant layers 4 is 8, 10, 12 or 15. In this way, a balance can be achieved between the thickness, wear resistance and hardness of the coating, so that the coating can have greater hardness and wear resistance in a thinner state.

[0045] In the embodiment of the present disclosure, by setting the thickness of the main wear-resistant layer 4 to between 200 and 600 nanometers, setting the thickness ratio of the second wear-resistant sub-layer 42 to the first wear-resistant sub-layer 41 to between 0.5 and 3, and setting the number of the main wear-resistant layers 4 to between 8 and 15, the grain sizes of the first wear-resistant sub-layer 41 and the second wear-resistant sub-layer 42 can be effectively refined, which not only helps to improve the mechanical properties of the main wear-resistant layer 4, but also can improve the density and uniformity of the main wear-resistant layer 4.

[0046] In one embodiment of the present disclosure, the thickness of the transition layer 2 is between 100 and 320 nanometers. For example, the thickness of the transition layer 2 is 100 nanometers, 150 nanometers, 200 nanometers, 250 nanometers, 300 nanometers or 320 nanometers. It should be noted that in other embodiments of the present disclosure, the thickness of the transition layer 2 is not limited thereto.

[0047] In one embodiment of the present disclosure, the material of the transition layer 2 is a titanium-molybdenum alloy. For example, the transition layer 2 can be formed by depositing titanium and molybdenum in an atmosphere containing argon. In one embodiment of the present disclosure, the thickness of the connecting layer 3 is between 100 and 800 nanometers. For example, the thickness of the connecting layer 3 is 100 nanometers, 200 nanometers, 300 nanometers, 500 nanometers, 700 nanometers or 800 nanometers. It should be noted that in other embodiments of the present disclosure, the thickness of the connecting layer 3 is not limited thereto.

[0048] In one embodiment of the present disclosure, the material of the connection layer 3 is titanium, molybdenum, and nitrogen. For example, the connection layer 3 can be formed by depositing titanium and molybdenum in an atmosphere containing argon and nitrogen.

[0049] In one embodiment of the present disclosure, the thickness of the lubricating layer 5 is between 1.5 and 3.9 microns. For example, the thickness of the lubricating layer 5 is 1.5 microns, 2.0 microns, 2.5 microns, 3.0 microns, 3.5 microns or 3.9 microns. It should be noted that in other disclosed embodiments, the thickness of the lubricating layer 5 is not limited thereto.

[0050] In one embodiment of the present disclosure, the material of the lubricating layer 5 is graphite. Furthermore, titanium and copper are added to the lubricating layer 5 to improve the performance of the lubricating layer 5. For example, the lubricating layer 5 can be formed by depositing titanium, copper and carbon in an acetylene atmosphere. As an example, the thickness of the transition layer is between 100 and 320 nanometers; the thickness of the connecting layer is between 100 and 800 nanometers; and the thickness of the lubricating layer is between 1.6 and 3.9 micrometers.

[0051] In one embodiment of the present disclosure, the material of the transition layer 2 is titanium-molybdenum alloy; the material of the connection layer 3 is titanium-molybdenum-nitrogen; and the material of the lubricating layer 5 is graphite (co-doped with titanium and copper elements).

[0052] In one embodiment of the present disclosure, the material of the substrate 1 is at least one of titanium alloy, stainless steel, bearing steel, cast iron or hard alloy. For example, the material of the substrate 1 is titanium alloy, stainless steel, bearing steel, cast iron or hard alloy. In other embodiments, the material of the substrate 1 is not limited thereto.

[0053] In one embodiment of the present disclosure, the total thickness of the titanium-molybdenum-based anti-friction and wear-resistant coating is between 4.4 and 9.1 microns. For example, the total thickness of the titanium-molybdenum-based anti-friction and wear-resistant coating is 4.4 microns, 5.0 microns, 5.6 microns, 6.2 microns, 6.8 microns, 7.4 microns, 8.0 microns, 8.6 microns or 9.1 microns. It should be noted that in other embodiments, the total thickness of the titanium-molybdenum-based anti-friction and wear-resistant coating is not limited thereto.

[0054] In one embodiment of the present disclosure, the hardness of the titanium-molybdenum-based anti-friction and wear-resistant coating is above 1600 Vickers hardness.

[0055] In one embodiment of the present disclosure, the friction coefficient of the titanium-molybdenum-based anti-friction and wear-resistant coating is below 0.15.

[0056] In one embodiment of the present disclosure, the wear rate of the titanium-molybdenum-based anti-friction and wear-resistant coating is 2.5×10 -6 mm 3 / Nm or less.

[0057] As an example, the hardness of the titanium-molybdenum-based anti-friction and wear-resistant coating is above 1600 Vickers hardness, the friction coefficient of the titanium-molybdenum-based anti-friction and wear-resistant coating is below 0.15, and the wear rate of the titanium-molybdenum-based anti-friction and wear-resistant coating is below 2.5×10 -6 mm 3 / Nm or less. That is, the coating provided by the present disclosure has good friction reduction, wear resistance and corrosion resistance.

[0058] Figure 2 Schematic diagram of the method for preparing a titanium-molybdenum-based anti-friction and wear-resistant coating in the embodiment of the present disclosure. Figure 2 In the embodiment of the present disclosure, the method for preparing the titanium-molybdenum-based anti-friction and wear-resistant coating includes the following steps S1 to S6.

[0059] S1: providing a substrate 1.

[0060] Specifically, the substrate 1 is pre-cleaned by using a solvent. The cleaning process of the substrate 1 using a solvent is as follows: the substrate 1 is ultrasonically cleaned by using acetone, an alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0061] S11: Preparation of the vacuum chamber before use: Place the dried substrate 1, titanium target, molybdenum target, copper target and carbon target into the vacuum chamber, and obtain the corresponding target material and substrate 1 in the vacuum chamber.

[0062] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target must not be less than 99%.

[0063] It should be noted that the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel.

[0064] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The process of evacuating and heating the vacuum chamber is as follows: evacuating the vacuum chamber to a vacuum degree of 3×10 -4 Pa~8×10 -3 Pa (For example, evacuate the vacuum chamber to a vacuum degree of 3×10 -4 Pa, 4×10 -4 Pa, 5×10 - 4 Pa, 7×10 -4 Pa is or 8×10 -4 Pa) and then heated to 200°C to 420°C (for example, the heating temperature is 200°C, 300°C, 400°C or 420°C) and kept warm until the vacuum is restored to 3×10 -4 Pa~8×10-3 Pa (for example, the vacuum degree is restored to 3×10 -4 Pa, 4×10 -4 Pa, 5×10 -4 Pa, 6×10 -4 Pa or 8×10 -4 Pa).

[0065] The substrate 1 treated in step S12 is cleaned by argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 200°C to 420°C (for example, the heating temperature is 200°C, 300°C, 400°C or 420°C), the argon gas channel is opened, the argon gas pressure is adjusted to 1.5Pa to 2Pa (for example, the argon gas pressure is 1.5Pa, 1.6Pa, 1.8Pa or 2.0Pa), the substrate 1 bias is set to -700V to -1250V (for example, the substrate 1 bias is -700V, -800V, -1000V, -1200V or -1250V), and the substrate 1 is cleaned by argon ion glow.

[0066] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0067] The process of preparing transition layer 2 is: keep the argon gas channel open, adjust the argon gas channel pressure to 0.5Pa~1Pa (for example, the argon gas pressure is 0.5Pa, 0.6Pa, 0.8Pa or 1.0Pa), adjust the substrate 1 bias to -75V~-150V (for example, the substrate 1 bias is -75V, -90V, -110V, or -150V), turn on the titanium target and the molybdenum target, adjust the power of the titanium target and the molybdenum target to 100W~180W (for example, adjust the power of the titanium target and the molybdenum target to 100W, 120W, 160W or 180W), and deposit the transition layer 2 (the material of the transition layer 2 is titanium-molybdenum alloy).

[0068] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0069] Maintain the argon channel valve open, maintain the argon pressure at 0.5Pa~1Pa (for example, the argon pressure is 0.5Pa, 0.6Pa, 0.8Pa or 1.0Pa), open the nitrogen channel, adjust the total nitrogen pressure to 0.8Pa~1.5Pa (for example, the argon pressure is 0.8Pa, 1.0Pa, 1.2Pa or 1.5Pa), maintain the substrate 1 bias at -75V~-150V (for example, the substrate 1 bias is -75V, -90V, -110V, or -150V), maintain the power of the titanium target and the molybdenum target at 100W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0070] S4: preparing at least one main wear-resistant layer 4 on the side of the connecting layer 3 away from the transition layer 2; wherein any one of the main wear-resistant layers 4 includes a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 which are stacked.

[0071] Specifically, the temperature in the vacuum chamber is adjusted to the first temperature range; the bias of the substrate 1 is adjusted to the first bias range; the power of the titanium target and the molybdenum target is adjusted to the first power; the gas pressure of the argon channel is adjusted to the first pressure; the gas pressure of the nitrogen channel is adjusted to the second pressure; the power of the copper target is adjusted to the second power, the copper target is periodically turned on, and the first wear-resistant sub-layer 41 and the second wear-resistant sub-layer 42 are alternately deposited on the connecting layer 3.

[0072] As an example, the temperature of the vacuum chamber is maintained at 200°C to 420°C (for example, the temperature in the vacuum chamber is maintained at 200°C, 250°C, 300°C, 300°C or 420°C), the bias voltage of the substrate 1 is maintained at -75V to -150V (for example, the bias voltage of the substrate 1 is -75V, -90V, -110V or -150V), the power of the titanium target and the molybdenum target is maintained at 100W to 180W (for example, the power of the titanium target and the molybdenum target is adjusted to 100W, 120W, 160W or 180W), and the partial pressure of the argon gas introduced into the argon gas channel is maintained at 0.5Pa to 1Pa (for example, For example, the argon pressure is 0.5Pa, 0.6Pa, 0.8Pa or 1.0Pa), the nitrogen channel is kept open, the pressure of the nitrogen channel is adjusted to a total pressure of 0.8Pa~1.5Pa (for example, the nitrogen pressure is 0.8Pa, 1.0Pa, 1.2Pa or 1.5Pa), the copper target power is set to 80W~120W (for example, the power of the copper target is 80W, 100W or 120W), and titanium, molybdenum, copper and nitrogen (forming a first sub-wear-resistant layer 41) and titanium, molybdenum and nitrogen (forming a second sub-wear-resistant layer 42) are alternately deposited on the connecting layer 3 by periodically opening and closing the copper target to form a multi-layer main wear-resistant layer 4.

[0073] S5: preparing a lubricating layer 5 on the side of the main wear-resistant layer 4 away from the connecting layer 3 .

[0074] Maintain the preparation temperature in the vacuum chamber to the first temperature range; adjust the substrate 1 bias to the second bias range; turn off the molybdenum target, and keep the titanium target and the copper target in the on state, wherein the power of the titanium target is adjusted to the third power; adjust the power of the copper target to the fourth power; close the nitrogen channel; adjust the gas pressure of the acetylene channel to the second gas pressure, adjust the power of the carbon target to the fifth power, and form a lubricating layer 5 on the main wear-resistant layer 4.

[0075] Specifically, the temperature in the vacuum chamber is maintained at 200° C. to 420° C. (for example, the temperature in the vacuum chamber is maintained at 200° C., 250° C., 300° C., 300° C. or 420° C.), the bias value of the substrate 1 is adjusted to -150V to -200V (for example, the substrate 1 is biased to -150V, -160V, -180V or -200V), the molybdenum target is turned off, the titanium target and the copper target are kept on, and the power of the titanium target is adjusted to 50W to 80W (for example, the power of the titanium target is 50W, 60W, 70W or 80W), Adjust the copper target power to 30W~60W (for example, the power of the titanium target is 30W, 40W, 50W or 60W), close the nitrogen channel, open the acetylene channel, and adjust the acetylene partial pressure to 0.2Pa~1.3Pa (for example, the acetylene partial pressure is 0.2Pa, 0.6Pa, 0.8Pa or 1.3Pa), open the carbon target, set the carbon target power to 30~60W (for example, the power of the titanium target is 30W, 40W, 50W or 60W), and form a co-doped lubricating layer 5 on the main wear-resistant layer 4.

[0076] It should be noted that, in this embodiment, the material of the lubricating layer 5 is graphite. Furthermore, in order to improve the performance of the lubricating layer 5, the lubricating layer 5 also contains titanium and copper elements.

[0077] S6: After the lubricating layer 5 is deposited, the substrate 1 is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating.

[0078] The following combines multiple embodiments and methods for preparing coatings of multiple embodiments to verify the characteristics of the coatings.

[0079] Embodiment 1:

[0080] The coating disclosed in the first embodiment can be prepared in the following manner:

[0081] S1: Provide a substrate 1 (the material of the substrate 1 is titanium alloy).

[0082] At the same time, the titanium alloy substrate 1 needs to be pre-treated. Specifically, the substrate 1 is pre-cleaned. The substrate 1 is first pre-cleaned with a solvent. The cleaning process of the substrate 1 using a solvent is: acetone, alcohol solution and deionized water are used to ultrasonically clean the substrate 1 in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0083] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0084] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target shall not be less than 99%. It should be noted that the vacuum chamber has a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel and an acetylene channel;

[0085] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The process of evacuating and heating the vacuum chamber is as follows: evacuating the vacuum chamber to a vacuum degree of 3×10 -4 Pa and then heated to 300 °C and kept warm until the vacuum was restored to 3 × 10 -4 Pa.

[0086] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 300°C, the argon gas channel is opened, the argon gas pressure is adjusted to 1.5 Pa, the substrate 1 bias voltage is set to -700V, and the substrate 1 is cleaned with argon ion glow.

[0087] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0088] The process of preparing the transition layer 2 is as follows: keep the argon gas channel open, adjust the argon gas channel pressure to 0.5 Pa, adjust the substrate 1 bias voltage to -75 V, turn on the titanium target and the molybdenum target, adjust the power of the titanium target and the molybdenum target to 100 W, and deposit the transition layer 2 (the material of the transition layer 2 is titanium-molybdenum alloy). In this step, the thickness of the deposited transition layer 2 is 240 nanometers.

[0089] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0090] Keep the argon channel valve open, maintain the argon pressure at 0.5Pa, open the nitrogen channel, adjust the total nitrogen pressure to 0.8Pa, maintain the substrate 1 bias at -75V, maintain the power of the titanium target and molybdenum target at 100W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0091] In this step, the connection layer 3 is deposited to a thickness of 400 nanometers.

[0092] S4: preparing at least one main wear-resistant layer 4 on the side of the connecting layer 3 away from the transition layer 2; wherein any one of the main wear-resistant layers 4 includes a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 which are stacked.

[0093] Specifically, the temperature of the vacuum chamber is maintained at 300°C, the bias voltage of the substrate 1 is maintained at -75V, the power of the titanium target and the molybdenum target is maintained at 100W, the partial pressure of the argon gas introduced into the argon channel is maintained at 0.5Pa, the nitrogen channel is kept open, the gas pressure of the nitrogen channel is adjusted to a total gas pressure of 0.8Pa, the power of the copper target is set to 80W, and by periodically opening and closing the copper target, titanium, molybdenum, copper and nitrogen (forming a first sub-wear-resistant layer 41) and titanium, molybdenum and nitrogen (forming a second sub-wear-resistant layer 42) are alternately deposited on the connecting layer 3 to form a multi-layer main wear-resistant layer 4.

[0094] In this step, the thickness of the main wear-resistant layer 4 is 3.2 microns.

[0095] S5: preparing a lubricating layer 5 on the side of the main wear-resistant layer 4 away from the connecting layer 3 .

[0096] Specifically, the temperature in the vacuum chamber is maintained at 300° C., the bias value of the substrate 1 is adjusted to -150V, the molybdenum target is turned off, the titanium target and the copper target are kept on, the power of the titanium target is adjusted to 50W, the power of the copper target is adjusted to 30W, the nitrogen channel is closed, the acetylene channel is opened, and the acetylene partial pressure is adjusted to 0.2Pa, the carbon target is opened, and the power of the carbon target is set to 30W, and the co-doped lubricating layer 5 is formed on the main wear-resistant layer 4. It should be noted that in this embodiment, the material of the lubricating layer 5 is graphite, and further, in order to improve the performance of the lubricating layer 5, the lubricating layer 5 also contains titanium and copper elements.

[0097] In this step, the thickness of the lubricating layer 5 is 3.5 μm.

[0098] S6: After the lubricating layer 5 is deposited, the substrate 1 is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating.

[0099] For Example 1, when the material of the substrate 1 is titanium alloy, the hardness of the coating is 1600 HV and the total thickness is 7.34 μm. Furthermore, the reciprocating friction test shows that the friction coefficient of the coating is 0.11 and the wear rate is 7.6×10 -7 mm 3 / Nm. Figure 3 This is the wear scar morphology on the surface of the titanium-molybdenum-based anti-friction and wear-resistant coating in this embodiment. It can be seen that the wear scar morphology of the coating is dense and uniform, without fatigue and cracks, reflecting excellent lubrication and wear resistance.

[0100] Embodiment 2:

[0101] S1: providing a substrate 1 (the material of the substrate 1 is stainless steel).

[0102] At the same time, the stainless steel substrate 1 needs to be pre-treated. Specifically, the substrate 1 is pre-cleaned. The substrate 1 is first pre-cleaned with a solvent. The cleaning process of the substrate 1 with a solvent is: ultrasonically clean the substrate 1 with acetone, alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece rack in the cavity.

[0103] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0104] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target shall not be less than 99%. It should be noted that the vacuum chamber has a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel and an acetylene channel.

[0105] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The evacuation and heating process in the vacuum chamber is as follows: the vacuum chamber is evacuated to a vacuum degree of 8×10 -3 Pa and then heated to 420℃ and kept warm until the vacuum was restored to 8×10 -3 Pa.

[0106] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: maintaining the temperature in the vacuum chamber at 420°C, opening the argon gas channel, adjusting the argon gas pressure to 2Pa, setting the substrate 1 bias voltage to 1250V, and cleaning the substrate 1 with argon ion glow.

[0107] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0108] The process of preparing transition layer 2 is: keep the argon channel open, adjust the argon channel pressure to 1Pa, adjust the substrate 1 bias to -150V, turn on the titanium target and molybdenum target, adjust the power of the titanium target and the molybdenum target to 180W, and deposit transition layer 2 (the material of transition layer 2 is titanium-molybdenum alloy).

[0109] In this step, the transition layer 2 is deposited to a thickness of 100 nanometers.

[0110] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0111] Maintain the argon channel valve open, maintain the argon pressure at 1Pa, open the nitrogen channel, adjust the total nitrogen pressure to 1.5Pa, maintain the substrate 1 bias at -150V, maintain the power of the titanium target and molybdenum target at 180W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0112] In this step, the connection layer 3 is deposited to a thickness of 100 nanometers.

[0113] S4: preparing at least one main wear-resistant layer 4 on the side of the connecting layer 3 away from the transition layer 2; wherein any one of the main wear-resistant layers 4 comprises a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 stacked thereon;

[0114] Specifically, the temperature of the vacuum chamber is maintained at 420°C, the bias voltage of the substrate 1 is maintained at -150V, the power of the titanium target and the molybdenum target is maintained at 180W, the partial pressure of the argon gas introduced into the argon channel is maintained at 1Pa, the nitrogen channel is kept open, the gas pressure of the nitrogen channel is adjusted to a total gas pressure of 1.5Pa, the power of the copper target is set to 120W, and titanium, molybdenum, copper and nitrogen (forming a first sub-wear-resistant layer 41) and titanium, molybdenum and nitrogen (forming a second sub-wear-resistant layer 42) are alternately deposited on the connecting layer 3 by periodically opening and closing the copper target to form a multi-layer main wear-resistant layer 4.

[0115] In this step, the thickness of the main wear-resistant layer 4 is 2.0 microns.

[0116] S5: preparing a lubricating layer 5 on the side of the main wear-resistant layer 4 away from the connecting layer 3 .

[0117] Specifically, the temperature in the vacuum chamber is maintained at 420° C., the bias value of the substrate 1 is adjusted to -200 V, the molybdenum target is turned off, the titanium target and the copper target are kept on, the titanium target power is adjusted to 80 W, the copper target power is adjusted to 60 W, the nitrogen channel is closed, the acetylene channel is opened, and the acetylene partial pressure is adjusted to 1.3 Pa, the carbon target is opened, and the carbon target power is set to 60 W (, and the co-doped lubricating layer 5 is formed on the main wear-resistant layer 4. It should be noted that, in this embodiment, the material of the lubricating layer 5 is graphite. Further, in order to improve the performance of the lubricating layer 5, the lubricating layer 5 also contains titanium and copper elements.

[0118] In this step, the thickness of the lubricating layer 5 is 2.2 μm.

[0119] S6: After the lubricating layer 5 is deposited, the substrate 1 is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating.

[0120] For Example 2, after testing, when the substrate 1 is made of stainless steel, the hardness of the coating is 1721 HV and the total thickness is 4.4 μm. Furthermore, after reciprocating friction test, the friction coefficient is 0.13 and the wear rate is 2.5×10 -6 mm 3 / Nm.

[0121] Embodiment three:

[0122] S1: providing a substrate 1 (the material of the substrate 1 is cast iron). Meanwhile, the cast iron substrate 1 needs to be pre-treated.

[0123] Specifically, the substrate 1 is pre-cleaned by using a solvent. The cleaning process of the substrate 1 using a solvent is as follows: the substrate 1 is ultrasonically cleaned by using acetone, an alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0124] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0125] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target must not be less than 99%.

[0126] It should be noted that the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel.

[0127] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The evacuation and heating process in the vacuum chamber is as follows: the vacuum chamber is evacuated to a vacuum degree of 7×10 -4 Pa and then heated to 200 °C and kept warm until the vacuum was restored to 7 × 10 -4 Pa.

[0128] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 200°C, the argon gas channel is opened, the argon gas pressure is adjusted to 1.7 Pa, the substrate 1 bias voltage is set to -1000V, and the substrate 1 is cleaned with argon ion glow.

[0129] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0130] The process of preparing transition layer 2 is: keep the argon channel open, adjust the argon channel pressure to 0.7Pa, adjust the substrate 1 bias to -100V, turn on the titanium target and molybdenum target, adjust the power of the titanium target and the molybdenum target to 150W, and deposit transition layer 2 (the material of transition layer 2 is titanium-molybdenum alloy).

[0131] In this step, the transition layer 2 is deposited to a thickness of 100 nanometers.

[0132] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1;

[0133] Maintain the argon channel valve open, maintain the argon pressure at 0.7Pa, open the nitrogen channel, adjust the total nitrogen pressure to 1.2Pa, maintain the substrate 1 bias at -100V, maintain the power of the titanium target and molybdenum target at 150W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0134] In this step, the connection layer 3 is deposited to a thickness of 600 nanometers.

[0135] S4: preparing at least one main wear-resistant layer 4 on the side of the connecting layer 3 away from the transition layer 2; wherein any one of the main wear-resistant layers 4 comprises a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 which are stacked;

[0136] Specifically, the temperature of the vacuum chamber is maintained at 200°C, the bias voltage of the substrate 1 is maintained at -100V, the power of the titanium target and the molybdenum target is maintained at 150W, the partial pressure of the argon gas introduced into the argon channel is maintained at 0.7Pa, the nitrogen channel is kept open, the gas pressure of the nitrogen channel is adjusted to a total gas pressure of 1.2Pa, the power of the copper target is set to 100W, and by periodically opening and closing the copper target, titanium, molybdenum, copper and nitrogen (forming a first sub-wear-resistant layer 41) and titanium, molybdenum and nitrogen (forming a second sub-wear-resistant layer 42) are alternately deposited on the connecting layer 3 to form a multi-layer main wear-resistant layer 4.

[0137] In this step, the thickness of the main wear-resistant layer 4 is 4.5 microns.

[0138] S5: preparing a lubricating layer 5 on the side of the main wear-resistant layer 4 away from the connecting layer 3 .

[0139] Specifically, the temperature in the vacuum chamber is maintained at 200° C., the bias value of the substrate 1 is adjusted to -175V, the molybdenum target is turned off, the titanium target and the copper target are kept on, the power of the titanium target is adjusted to 70W, the power of the copper target is adjusted to 50W, the nitrogen channel is closed, the acetylene channel is opened, and the acetylene partial pressure is adjusted to 0.8Pa, the carbon target is opened, and the power of the carbon target is set to 45W, and the co-doped lubricating layer 5 is formed on the main wear-resistant layer 4. It should be noted that in this embodiment, the material of the lubricating layer 5 is graphite, and further, in order to improve the performance of the lubricating layer 5, the lubricating layer 5 also contains titanium and copper elements.

[0140] In this step, the thickness of the lubricating layer 5 was 3.9 μm.

[0141] S6: After the lubricating layer 5 is deposited, the substrate 1 is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating.

[0142] After testing, when the material of the substrate 1 is cast iron, the hardness of the coating under this substrate 1 is 1856HV, the total thickness is 9.1μm, and the friction coefficient is 0.14 and the wear rate is 1.3×10 -6 mm 3 / Nm.

[0143] For Example 3, when the substrate material is cast iron, the hardness of the coating is 1856 HV, the total thickness is 9.1 μm, and the friction coefficient is 0.14 and the wear rate is 1.3×10 -6 mm 3 / Nm.

[0144] Embodiment 4:

[0145] S1: providing a substrate 1 (the material of the substrate 1 is cemented carbide). Meanwhile, the cemented carbide substrate 1 needs to be pre-processed.

[0146] Specifically, the substrate 1 is pre-cleaned by using a solvent. The cleaning process of the substrate 1 using a solvent is as follows: the substrate 1 is ultrasonically cleaned by using acetone, an alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0147] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0148] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target must not be less than 99%.

[0149] It should be noted that the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel.

[0150] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The evacuation and heating process in the vacuum chamber is as follows: the vacuum chamber is evacuated to a vacuum degree of 2×10 -3 Pa and then heated to 300 °C and kept warm until the vacuum was restored to 2 × 10 -3 Pa.

[0151] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 300°C, the argon gas channel is opened, the argon gas pressure is adjusted to 1.8 Pa, the substrate 1 bias voltage is set to -1000V, and the substrate 1 is cleaned with argon ion glow.

[0152] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0153] The process of preparing transition layer 2 is: keep the argon channel open, adjust the argon channel pressure to 0.8Pa, adjust the substrate 1 bias to -125V, turn on the titanium target and molybdenum target, adjust the power of the titanium target and molybdenum target to 150W, and deposit transition layer 2 (the material of transition layer 2 is titanium-molybdenum alloy).

[0154] In this step, the thickness of the deposited transition layer 2 is 3200 nanometers.

[0155] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0156] Maintain the argon channel valve open, maintain the argon pressure at 0.8Pa, open the nitrogen channel, adjust the total nitrogen pressure to 1.3Pa, maintain the substrate 1 bias at -125V, maintain the power of the titanium target and molybdenum target at 150W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0157] In this step, the connection layer 3 is deposited to a thickness of 800 nanometers.

[0158] S4: preparing at least one main wear-resistant layer 4 on the side of the connecting layer 3 away from the transition layer 2; wherein any one of the main wear-resistant layers 4 includes a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 which are stacked.

[0159] Specifically, the temperature of the vacuum chamber is maintained at 300°C, the bias voltage of the substrate 1 is maintained at -125V, the power of the titanium target and the molybdenum target is maintained at 150W, the partial pressure of the argon gas introduced into the argon channel is maintained at 0.8Pa, the nitrogen channel is kept open, the gas pressure of the nitrogen channel is adjusted to a total gas pressure of 1.3Pa, the power of the copper target is set to 80W, and by periodically opening and closing the copper target, titanium, molybdenum, copper and nitrogen (forming a first sub-wear-resistant layer 41) and titanium, molybdenum and nitrogen (forming a second sub-wear-resistant layer 42) are alternately deposited on the connecting layer 3 to form a multi-layer main wear-resistant layer 4.

[0160] In this step, the thickness of the main wear-resistant layer 4 is 5.4 microns.

[0161] S5: preparing a lubricating layer 5 on the side of the main wear-resistant layer 4 away from the connecting layer 3 .

[0162] Specifically, the temperature in the vacuum chamber is maintained at 300° C., the bias value of the substrate 1 is adjusted to -200V, the molybdenum target is turned off, the titanium target and the copper target are kept on, the power of the titanium target is adjusted to 80W, the power of the copper target is adjusted to 60W, the nitrogen channel is closed, the acetylene channel is opened, and the acetylene partial pressure is adjusted to 0.6Pa, the carbon target is opened, and the power of the carbon target is set to 50W, and the co-doped lubricating layer 5 is formed on the main wear-resistant layer 4. It should be noted that in this embodiment, the material of the lubricating layer 5 is graphite, and further, in order to improve the performance of the lubricating layer 5, the lubricating layer 5 also contains titanium and copper elements.

[0163] In this step, the thickness of the lubricating layer 5 is 1.6 μm.

[0164] S6: After the lubricating layer 5 is deposited, the substrate 1 is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating.

[0165] After testing, when the material of the substrate 1 is cemented carbide, the hardness of the coating under this substrate 1 is 1786HV, and the total thickness is 8.12 microns. Furthermore, after reciprocating friction test, the friction coefficient is 0.13 and the wear rate is 2.1×10 -6 mm 3 / Nm.

[0166] Embodiment five:

[0167] S1: providing a substrate 1 (the material of the substrate 1 is bearing steel). Meanwhile, the bearing steel substrate 1 needs to be pre-processed.

[0168] Specifically, the substrate 1 is pre-cleaned by using a solvent. The cleaning process of the substrate 1 using a solvent is as follows: the substrate 1 is ultrasonically cleaned by using acetone, an alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0169] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0170] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target must not be less than 99%.

[0171] It should be noted that the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel.

[0172] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The evacuation and heating process in the vacuum chamber is as follows: the vacuum chamber is evacuated to a vacuum degree of 5×10 -3 Pa and then heated to 300 °C and kept warm until the vacuum was restored to 5 × 10 -3 Pa.

[0173] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 300°C, the argon gas channel is opened, the argon gas pressure is adjusted to 1.8 Pa, the substrate 1 bias voltage is set to -1000V, and the substrate 1 is cleaned with argon ion glow.

[0174] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0175] The process of preparing transition layer 2 is: keep the argon channel open, adjust the argon channel pressure to 0.5Pa, adjust the substrate 1 bias to -75V, turn on the titanium target and molybdenum target, adjust the power of the titanium target and the molybdenum target to 100W, and deposit transition layer 2 (the material of transition layer 2 is titanium-molybdenum alloy).

[0176] In this step, the transition layer 2 is deposited to a thickness of 240 nanometers.

[0177] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0178] Keep the argon channel valve open, maintain the argon pressure at 0.5Pa, open the nitrogen channel, adjust the total nitrogen pressure to 1.0Pa, maintain the substrate 1 bias at -75V, maintain the power of the titanium target and molybdenum target at 100W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0179] In this step, the connection layer 3 is deposited to a thickness of 400 nanometers.

[0180] S4: preparing at least one main wear-resistant layer 4 on the side of the connecting layer 3 away from the transition layer 2; wherein any one of the main wear-resistant layers 4 includes a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 which are stacked.

[0181] Specifically, the temperature of the vacuum chamber is maintained at 300°C, the bias voltage of the substrate 1 is maintained at -75V, the power of the titanium target and the molybdenum target is maintained at 100W, the partial pressure of the argon gas introduced into the argon channel is maintained at 0.5Pa, the nitrogen channel is kept open, the gas pressure of the nitrogen channel is adjusted to a total gas pressure of 1.0Pa, the power of the copper target is set to 80W, and by periodically opening and closing the copper target, titanium, molybdenum, copper and nitrogen (forming a first sub-wear-resistant layer 41) and titanium, molybdenum and nitrogen (forming a second sub-wear-resistant layer 42) are alternately deposited on the connecting layer 3 to form a multi-layer main wear-resistant layer 4.

[0182] In this step, the thickness of the main wear-resistant layer 4 is 3.6 microns.

[0183] S5: preparing a lubricating layer 5 on the side of the main wear-resistant layer 4 away from the connecting layer 3 .

[0184] Specifically, the temperature in the vacuum chamber is maintained at 300° C., the bias value of the substrate 1 is adjusted to -175V, the molybdenum target is turned off, the titanium target and the copper target are kept on, the power of the titanium target is adjusted to 50W, the power of the copper target is adjusted to 30W, the nitrogen channel is closed, the acetylene channel is opened, and the acetylene partial pressure is adjusted to 1.0Pa, the carbon target is opened, and the power of the carbon target is set to 50W, and the co-doped lubricating layer 5 is formed on the main wear-resistant layer 4. It should be noted that in this embodiment, the material of the lubricating layer 5 is graphite, and further, in order to improve the performance of the lubricating layer 5, the lubricating layer 5 also contains titanium and copper elements.

[0185] In this step, the thickness of the lubricating layer 5 is 3.8 μm.

[0186] S6: After the lubricating layer 5 is deposited, the substrate 1 is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating.

[0187] For Example 5, when the material of the substrate 1 is bearing steel, the hardness of the coating is 1691 HV and the total thickness is 8.04 μm. After the reciprocating friction test, the friction coefficient is 0.1 and the wear rate is 7.6×10 - 7 mm 3 / Nm.

[0188] It should be noted that the embodiments of the present disclosure can use physical vapor deposition technology to manufacture each film layer of the titanium-molybdenum-based anti-friction and wear-resistant coating. In this way, the composition of each film layer of the coating can be accurately controlled to achieve densification and uniformity of the coating structure, while not affecting the size, structure and mechanical properties of the workpiece, and no subsequent processing and heat treatment are required, which is simple to operate and economical.

[0189] In order to further verify the performance of the coating, the inventor conducted the following experiment: The experiment was divided into three groups of control experiments, which are set as comparative example 1, comparative example 2 and comparative example 3 for the sake of convenience.

[0190] The specific examples and preparation methods of Comparative Example 1, Comparative Example 2 and Comparative Example 3 are combined below to verify the characteristics of the coating.

[0191] Comparative Example 1:

[0192] Comparative Example 1 It should be noted that in Comparative Example 1, the coating includes a substrate 1, a transition layer 2, a connecting layer 3 and a main wear-resistant layer 4 (including a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42) which are stacked in sequence. It should be noted that the difference between Comparative Example 1 and the embodiment of the present disclosure is that Comparative Example 1 does not include a lubricating layer 5.

[0193] Furthermore, comparative example 1 can be prepared by the following method, which specifically includes steps S1 to S5.

[0194] S1: providing a substrate 1 (the material of the substrate 1 is titanium alloy). Meanwhile, the titanium alloy substrate 1 needs to be pre-processed.

[0195] Specifically, the substrate 1 is pre-cleaned by using a solvent. The cleaning process of the substrate 1 using a solvent is as follows: the substrate 1 is ultrasonically cleaned by using acetone, an alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0196] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0197] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target must not be less than 99%.

[0198] It should be noted that the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel.

[0199] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The process of evacuating and heating the vacuum chamber is as follows: evacuating the vacuum chamber to a vacuum degree of 3×10 -4 Pa and then heated to 300 °C and kept warm until the vacuum was restored to 3 × 10 -4 Pa.

[0200] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 300°C, the argon gas channel is opened, the argon gas pressure is adjusted to 1.5 Pa, the substrate 1 bias voltage is set to -700V, and the substrate 1 is cleaned with argon ion glow.

[0201] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0202] The process of preparing transition layer 2 is: keep the argon channel open, adjust the argon channel pressure to 0.5Pa, adjust the substrate 1 bias to -75V, turn on the titanium target and molybdenum target, adjust the power of the titanium target and the molybdenum target to 100W, and deposit transition layer 2 (the material of transition layer 2 is titanium-molybdenum alloy).

[0203] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0204] Keep the argon channel valve open, maintain the argon pressure at 0.5Pa, open the nitrogen channel, adjust the total nitrogen pressure to 0.8Pa, maintain the substrate 1 bias at -75V, maintain the power of the titanium target and molybdenum target at 100W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0205] S4: preparing at least one main wear-resistant layer 4 on the side of the connecting layer 3 away from the transition layer 2; wherein any one of the main wear-resistant layers 4 comprises a first wear-resistant sub-layer 41 and a second wear-resistant sub-layer 42 which are stacked;

[0206] Specifically, the temperature of the vacuum chamber is maintained at 300°C, the bias voltage of the substrate 1 is maintained at -75V, the power of the titanium target and the molybdenum target is maintained at 100W, the partial pressure of the argon gas introduced into the argon channel is maintained at 0.5Pa, the nitrogen channel is kept open, the gas pressure of the nitrogen channel is adjusted to a total gas pressure of 0.8Pa, the power of the copper target is set to 80W, and by periodically opening and closing the copper target, titanium, molybdenum, copper and nitrogen (forming a first sub-wear-resistant layer 41) and titanium, molybdenum and nitrogen (forming a second sub-wear-resistant layer 42) are alternately deposited on the connecting layer 3 to form a multi-layer main wear-resistant layer 4.

[0207] S5: subjecting the substrate 1 after the multi-layer main wear-resistant layer 4 to furnace insulation and cooling treatment to obtain a coating.

[0208] After many experiments, it is known that the hardness of the coating in comparative example 1 is 1821HV, the total thickness is 7.1 microns, and the friction coefficient is 0.25 and the wear rate is 7.2×10 -6 mm 3 / Nm. Figure 3 The wear scar morphology of the titanium-molybdenum-based anti-friction and wear-resistant coating surface in the embodiment of the present disclosure; Figure 4 The wear scar morphology of the titanium-molybdenum-based anti-friction and wear-resistant coating surface provided in Comparative Example 1 is shown in FIG. Figure 3 and Figure 4 It can be seen that in comparative example 1, the wear scar morphology of the coating is relatively rough, and the center of the wear scar presents partial wrinkles. By comparing the test results of comparative example 1 with the embodiment of the present disclosure, it can be concluded that the friction reduction function of the main wear-resistant layer 4 is limited, and plating a co-doped lubricating layer 5 (the lubricating layer 5 material is graphite, wherein the lubricating layer 5 is also doped with titanium and copper elements) on its surface is an effective means to further optimize the friction reduction and lubrication properties of the coating, thereby avoiding premature damage to the main wear-resistant layer 4.

[0209] Comparative Example 2:

[0210] It should be noted that in comparative example 2, the coating includes a substrate 1, a transition layer 2, and a connecting layer 3 which are stacked in sequence. The difference between comparative example 2 and the embodiment of the present disclosure is that comparative example 2 does not include a main wear-resistant layer 4 and a lubricating layer 5.

[0211] Comparative Example 2 is prepared by the following method, which specifically includes steps S1 to S4.

[0212] S1: providing a substrate 1 (the material of the substrate 1 is titanium alloy). Meanwhile, the titanium alloy substrate 1 needs to be pre-processed.

[0213] Specifically, the substrate 1 is pre-cleaned by using a solvent. The cleaning process of the substrate 1 using a solvent is as follows: the substrate 1 is ultrasonically cleaned by using acetone, an alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0214] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0215] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target must not be less than 99%.

[0216] It should be noted that the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel.

[0217] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The process of evacuating and heating the vacuum chamber is as follows: evacuating the vacuum chamber to a vacuum degree of 3×10 -4 Pa and then heated to 300 °C and kept warm until the vacuum was restored to 3 × 10 -4 Pa.

[0218] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 300°C, the argon gas channel is opened, the argon gas pressure is adjusted to 1.5 Pa, the substrate 1 bias voltage is set to -700V, and the substrate 1 is cleaned with argon ion glow.

[0219] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0220] The process of preparing transition layer 2 is: keep the argon channel open, adjust the argon channel pressure to 0.5Pa, adjust the substrate 1 bias to -75V, turn on the titanium target and molybdenum target, adjust the power of the titanium target and the molybdenum target to 100W, and deposit transition layer 2 (the material of transition layer 2 is titanium-molybdenum alloy).

[0221] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0222] Keep the argon channel valve open, maintain the argon pressure at 0.5Pa, open the nitrogen channel, adjust the total nitrogen pressure to 0.8Pa, maintain the substrate 1 bias at -75V, maintain the power of the titanium target and molybdenum target at 100W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0223] S4: After the connection layer 3 is deposited, the substrate 1 is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating. After multiple experiments, it is known that the hardness of the coating in comparative example 2 is 1321HV, the total thickness is 7.24 microns, and the friction coefficient of the coating is 0.27 and the wear rate is 9.7×10 -6 mm 3 / Nm. Through the test results of the embodiment of the present disclosure and comparative example 2, it can be concluded that the friction reduction and wear resistance of the connecting layer 3 is relatively low. It is necessary to further plate multiple main wear-resistant layers 4 and lubricating layers 5 on the connecting layer 3 to obtain excellent lubrication and wear resistance.

[0224] Comparative Example 3:

[0225] It should be noted that in comparative example 3, the coating includes a substrate 1, a transition layer 2, a connection layer 3 and a lubricating layer 5 stacked in sequence. It should be noted that the difference between comparative example 3 and the embodiment of the present disclosure is that the main wear-resistant layer 4 is not included in comparative example 3.

[0226] Comparative Example 3 is prepared by the following method, which specifically includes steps S1 to S5.

[0227] S1: providing a substrate 1 (the material of the substrate 1 is titanium alloy). Meanwhile, the titanium alloy substrate 1 needs to be pre-processed.

[0228] Specifically, the substrate 1 is pre-cleaned by using a solvent. The cleaning process of the substrate 1 using a solvent is as follows: the substrate 1 is ultrasonically cleaned by using acetone, an alcohol solution and deionized water in sequence. After the substrate 1 is cleaned, the substrate 1 is blown dry. After the pre-cleaning and drying, the substrate 1 is clamped on the workpiece holder in the cavity.

[0229] S11: Preparation of the vacuum chamber before use. The substrate 1, titanium target, molybdenum target, copper target and carbon target obtained in step S11 are placed in the vacuum chamber to obtain the target material and the substrate 1 in the vacuum chamber.

[0230] It should be noted that in this step, the mass purity of the titanium target, molybdenum target, copper target and carbon target must not be less than 99%.

[0231] It should be noted that the vacuum chamber is provided with a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel.

[0232] S12: The vacuum chamber containing the target material (e.g., titanium target, molybdenum target, copper target, and carbon target) and the substrate 1 in step S11 is evacuated and heated. The process of evacuating and heating the vacuum chamber is as follows: evacuating the vacuum chamber to a vacuum degree of 3×10 -4 Pa and then heated to 300 °C and kept warm until the vacuum was restored to 3 × 10 -4 Pa.

[0233] The substrate 1 processed in step S12 is cleaned with argon ion glow. The cleaning process is as follows: the temperature in the vacuum chamber is maintained at 300°C, the argon gas channel is opened, the argon gas pressure is adjusted to 1.5 Pa, the substrate 1 bias voltage is set to -700V, and the substrate 1 is cleaned with argon ion glow.

[0234] S2: preparing a transition layer 2 on the substrate 1 in a vacuum chamber.

[0235] The process of preparing transition layer 2 is: keep the argon channel open, adjust the argon channel pressure to 0.5Pa, adjust the substrate 1 bias to -75V, turn on the titanium target and molybdenum target, adjust the power of the titanium target and the molybdenum target to 100W, and deposit transition layer 2 (the material of transition layer 2 is titanium-molybdenum alloy).

[0236] S3: preparing a connection layer 3 on a side of the transition layer 2 away from the substrate 1 .

[0237] Keep the argon channel valve open, maintain the argon pressure at 0.5Pa, open the nitrogen channel, adjust the total nitrogen pressure to 0.8Pa, maintain the substrate 1 bias at -75V, maintain the power of the titanium target and molybdenum target at 100W, and deposit the connecting layer 3 (the material of the connecting layer 3 is titanium, molybdenum and nitrogen).

[0238] S4: preparing a lubricating layer 5 on the side of the connecting layer 3 away from the transition layer 2 .

[0239] Specifically, the temperature in the vacuum chamber is maintained at 300°C, the bias value of the substrate 1 is adjusted to -150V, the molybdenum target is turned off, the titanium target and the copper target are kept on, the power of the titanium target is adjusted to 50W, the power of the copper target is adjusted to 30W, the nitrogen channel is closed, the acetylene channel is opened, and the acetylene partial pressure is adjusted to 0.2Pa, the carbon target is turned on, and the power of the carbon target is set to 30W, and a co-doped lubricating layer 5 is formed on the connecting layer 3.

[0240] It should be noted that, in this embodiment, the material of the lubricating layer 5 is graphite. Furthermore, in order to improve the performance of the lubricating layer 5, the lubricating layer 5 also contains titanium and copper elements.

[0241] S5: the substrate 1 after the lubricating layer 5 is deposited is subjected to furnace heat preservation and cooling treatment to obtain a titanium-molybdenum-based anti-friction and wear-resistant coating.

[0242] After many experiments, it is known that the hardness of the coating in comparative example 3 is 1191HV, the total thickness is 7.44 microns, and the friction coefficient of the coating is 0.19 and the wear rate is 1.3×10 -5 mm 3 / Nm. It can be concluded from the test results of the embodiment of the present disclosure and the comparative example 3 that the multi-layer main wear-resistant layer 4 plays a role in strengthening the coating, thereby increasing the wear resistance of the coating and reducing the wear rate.

[0243] Through this comparative experiment, it can be concluded that the connecting layer 3, the multi-layer main wear-resistant layer 4 and the lubricating layer 5 complement each other and are indispensable, so that the coating has excellent mechanical properties and lubrication and wear-resistant characteristics.

[0244] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

Claims

1. A titanium-molybdenum-based anti-friction and wear-resistant coating, comprising a transition layer, a connecting layer, a multi-layer main wear-resistant layer and a lubricating layer stacked in sequence on one side of a substrate; The main wear-resistant layer includes a first wear-resistant sub-layer and a second wear-resistant sub-layer which are stacked; wherein, The first wear-resistant sub-layer and the second wear-resistant sub-layer are made of different materials.

2. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: The first wear-resistant sub-layer is a titanium, molybdenum, copper and nitrogen layer; the second wear-resistant sub-layer is a titanium, molybdenum and nitrogen layer.

3. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: In the same main wear-resistant layer, the thickness of the first wear-resistant sub-layer is between 100 and 400 nanometers, and the thickness of the second wear-resistant sub-layer is between 100 and 300 nanometers.

4. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: The thickness of the main wear-resistant layer is between 200 and 600 nanometers; the thickness ratio of the second wear-resistant sub-layer to the first wear-resistant sub-layer is between 0.5 and 3.

5. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: The number of the main wear-resistant layers is between 8 and 15.

6. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: The thickness of the transition layer is between 100 and 320 nanometers; the thickness of the connection layer is between 100 and 800 nanometers; and the thickness of the lubricating layer is between 1.6 and 3.9 micrometers.

7. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: The material of the substrate is at least one of titanium alloy, stainless steel, bearing steel, cast iron or cemented carbide.

8. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: The total thickness of the titanium-molybdenum-based anti-friction and wear-resistant coating is between 4.4 and 9.1 microns.

9. The titanium-molybdenum-based anti-friction and wear-resistant coating according to claim 1, wherein: The hardness of the titanium-molybdenum-based anti-friction and wear-resistant coating is above 1600 Vickers hardness, the friction coefficient of the titanium-molybdenum-based anti-friction and wear-resistant coating is below 0.15, and the wear rate of the titanium-molybdenum-based anti-friction and wear-resistant coating is below 2.5×10 -6 mm 3 / Nm or less.

10. A method for preparing a titanium-molybdenum-based friction-reducing and wear-resistant coating, comprising: providing a substrate; In a vacuum chamber, a transition layer is prepared on the substrate; wherein the vacuum chamber has a titanium target, a molybdenum target, a copper target, a carbon target, an argon channel, a nitrogen channel, and an acetylene channel; Prepare a connection layer on a side of the transition layer away from the substrate; At least one main wear-resistant layer is prepared on a side of the connecting layer away from the transition layer; wherein any one of the main wear-resistant layers comprises a first wear-resistant sub-layer and a second wear-resistant sub-layer which are stacked; A lubricating layer is prepared on a side of the main wear-resistant layer away from the connecting layer.